Influence of Stress and Burnout on Job Performance of Rural Bank Workers in the Upper Denkyira East Municipality - Gyasi, Isaac; Fia, Stephen Doh; Eyiah-Bediako, Sylvia (International Journal of Humanity and Social Sciences, 2025)
Purpose: The study examined the influence of stress and burnout on job performance of rural bank workers in the Upper Denkyira East Municipality in the Central Region of Ghana. Descriptive survey was used for the study. Methodology: The instrument used for the study was a questionnaire and it was made up of three sections. Section A included three items that assessed demographic characteristics of the respondents. Section B included 10 items that assessed causes of stress and burnout, whiles section C included 10 items that measured job performance. The accessible population for the study was 148 rural bank workers selected from four (4) rural banks in the Upper Denkyira East Municipality with a sample size of 108. Data were analysed using descriptive statistics (means and standard deviation) and inferential statistics (multiple linear regression and multivariate analysis of variance (MANOVA). Findings: The study revealed that the major causes of stress and burnout were excess workload and instability between one’s professional career and family life. Again, Stress and burnout were identified to have negative influence on the job performance of the rural bank workers and its effects did not differ in relation to age. It was recommended that workers be offered psychotherapy on how to handle their feelings to assist them minimise stress. Unique Contribution to Theory, Practice and Policy: It can be concluded that high stress and burnout among bank workers leads to poor output on their job. Again, strategies such as flexible shifts, adequate staffing, and better working conditions